Penggunaan Anggaran Sebagai Alat Pengendalian Kinerja Dalam Organisasi - Nur Widyawati; Purwanti (CV. ITTC INDONESIA, 2025)
A budget is a written plan regarding the activities of an organization that is expressed quantitatively and is generally expressed in units of money for a certain period. The budget can also be a coordination tool in the implementation of the activity plan of each part of the organization so that the resulting planning is an integrated and detailed overall company plan. This paper aims to find out the role of the use of budget as a performance control tool in organizations and the obstacles in budgeting as a performance control tool in organizations. In this study, the Study Literature Review (SLR) research method is used. This method is used to identify, review, evaluate, and interpret all studies. Based on the studies that have been carried out, it is known that in controlling the performance and evaluation of an organization, the budget acts as a benchmark to evaluate the actual performance of the company. There are several obstacles in budget to control the organization where there are several errors, namely market uncertainty, organizational commitment, and limited resources.